2020
DOI: 10.1002/jmri.27091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Biventricular Myocardial Velocity and Interventricular Dyssynchrony in Adult Patients During the First Year After Heart Transplantation

Abstract: BackgroundMagnetic resonance tissue phase mapping (TPM) measures three‐directional myocardial velocities of the left and right ventricle (LV, RV). This noninvasive technique may supplement endomyocardial biopsy (EMB) in monitoring grafts post‐heart transplantation (HTx).PurposeTo assess biventricular myocardial velocity alterations in grafts and investigate the relationship between velocities and acute cellular rejection (ACR) episodes.Study TypeProspective.SubjectsTwenty‐seven patients within 1 year post‐HTx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…23 Recently, several studies have demonstrated significant differences in biventricular global and regional velocities in heart transplant (HTx) patients (adult and pediatric) with and without transplant rejection. 15,16 Despite these studies demonstrating feasibility, the clinical translation of TPM is hampered by the requisite labor-intensive manual segmentation of the myocardial contours for all cardiac frames. In general, manual segmentation of TPM images is more challenging for the RV than the LV, because the former has a thinner wall, highly trabeculated myocardium, and epicardial fat partially superimposed on the myocardial wall.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Recently, several studies have demonstrated significant differences in biventricular global and regional velocities in heart transplant (HTx) patients (adult and pediatric) with and without transplant rejection. 15,16 Despite these studies demonstrating feasibility, the clinical translation of TPM is hampered by the requisite labor-intensive manual segmentation of the myocardial contours for all cardiac frames. In general, manual segmentation of TPM images is more challenging for the RV than the LV, because the former has a thinner wall, highly trabeculated myocardium, and epicardial fat partially superimposed on the myocardial wall.…”
Section: Introductionmentioning
confidence: 99%
“…CMR has the ability to non-invasively characterize intramyocardial function using techniques such as myocardial tagging, 4,5 strain-encoded (SENC) imaging, 6 cine displacement-encoded imaging with stimulated echoes (DENSE), 7,8 and tissue phase mapping (TPM). 9,10 These techniques have proven useful in diagnosing and monitoring abnormal myocardial function in a wide range of cardiovascular conditions including congenital heart diseases, 11,12 cardiotoxicities, 13,14 cardiac transplantation, [15][16][17] left ventricular dyssynchrony, 18,19 and various cardiomyopathies. [20][21][22] In this study, we will focus on TPM, which is a black-blood 2D cine phase contrast MRI pulse sequence with three-directional tissue velocity encoding for quantification of regional biventricular myocardial velocities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation